Adaptasi Kurikulum Merdeka Belajar Mata Pelajaran Bahasa Arab di SMP Takhassus Al-Qur’an Wonosobo - Rifqi Aulia Rahman; Miftahul Huda; Chairani Astina; Farah Faida (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2022)
The research departs from the problem that the Merdeka Belajar-Kampus Mengajar (MBKM) curriculum requires the principle of independent learning to be implemented in the management of education and learning. Meanwhile, the position of the Arabic subject at SMP Takhassus Al-Qur'an Wonosobo includes local content, the school's particular scientific core. In addition, the Arabic at the school has a specific orientation and learning outcomes. The paper aims to discuss and describe the management of the MBKM curriculum for the Arabic subject at Takhassus Al-Qur'an Middle School including planning, organizing, implementing, and evaluating the curriculum, and obstacles and efforts to overcome the barriers in the implementation of the curriculum management. The research method used is descriptive qualitative with case studies—data collection techniques using interviews, observation, and documentation. The research subjects were deputy head 1 of curriculum and Arabic teachers. The results of his research stated that the implementation of the Merdeka Learning curriculum for Arabic subjects had carried out an educational management flow that was by its stages, namely planning, organizing, implementing, and supervising. Even so, the obstacles in the implementation of the curriculum as the quality of education still encounter obstacles. These constraints require schools to apply the Free Learning curriculum with the principle of adaptation.